Concurrent lung adenocarcinoma and bladder diffuse large B-cell lymphoma: a case report and literature review. Issue 2 (February 2022) - Xu, Feng; Liang, Ying; Mo, Wen-Bin; Yan, Xiao-Jing; Zhang, Rui
Lung adenocarcinoma is one of the most common solid tumors, and diffuse large B-cell lymphoma (DLBCL) is the most common histological subtype of adult non-Hodgkin's lymphoma. Although extra-nodular lesions are frequently observed in patients with DLBCL, urinary bladder involvement is rare. We report the case of a 77-year-old woman with lung adenocarcinoma who was diagnosed with a second primary bladder DLBCL, 9 months after treatment with molecular targeted drugs. Simultaneous therapies for her lymphoma with lenalidomide and rituximab and a tyrosine kinase inhibitor therapy for her lung cancer were both effective. This result was consistent with previous reports suggesting that patients unable to tolerate intensive chemotherapy could benefit from targeted therapies. Current research into the use of lenalidomide for the treatment of lymphomas and solid tumors is promising in terms of exploring immunotherapy as an alternative option for patients with concurrent solid tumors and lymphomas who have poor tolerance to radiotherapy and chemotherapy.